Penyelesaian Sengketa Jual Beli Saham Perusahaan Dalam Perspektif Hukum Perdata - Sholihah Sholihah; Jamilah Jamilah; Marsella Marsella (JUNCTO: Jurnal Ilmiah Hukum, 2021)
The purpose of this research is to Know the Arrangements About Buying and Selling Shares, How Legitimate Selling and Selling of Shares. As well as to find out the Step in Settlement of Sales and Purchase Dispute of Company Shares This type of research in this journal is Normative Juridical. Arrangements for buying and selling of shares are regulated in law number 40 of 2007 concerning limited liability companies and the Civil Code and other laws. The validity of the Sale and Purchase of Shares is in accordance with the applicable regulations stipulated in Article 1457 of the Civil Code regarding the sale and purchase of shares while the shares are regulated in articles 40.41.42, and 43 KUHD. Settlement of disputes over the sale and purchase of company shares is resolved through 2 (two) channels, namely through deliberation and settlement through judicial channels.